KONSEP HOMO LUDENS DALAM PEMBELAJARAN BAHASA INDONESIA BERBASIS PERMAINAN: KAJIAN NARATIVE LITERATURE REVIEW - Muh. Rijalul Akbar; Syihabuddin; Ulfa Widayati; Dedi Irawan; Ramli (Jurnal PENEROKA, 2026)
This study aims to reconstruct gamification practices, often confined to mere structural aspects (pointsification), toward a deeper ontological understanding of play, while analyzing the convergence of educational philosophy with technological interventions. The scope of the research focuses on the implementation of the Homo Ludens concept within the context of Indonesian language learning spanning from 2020 to 2025. The methodology employed is a Narrative Literature Review (NLR), utilizing Johan Huizinga’s philosophical lens and a thematic analysis based on Roger Caillois’ typology of play. The research data model comprises 21 articles selected from the Crossref database, harvested via Harzing’s Publish or Perish, and screened through a Manual Quality Assessment (MQA) of reputable journals indexed in SINTA and Scopus. The findings reveal a fundamental paradigm shift wherein play has evolved into a core pedagogy, particularly within elementary education. Specifically, the study identifies a dominance of the agôn (competition) category, which enhances cognitive metrics but poses a risk of fostering transactional motivation. Conversely, the mimicry category and the concept of the magic circle prove vital in establishing a safe space for graceful failure, thereby reducing language anxiety. The study concludes that a balanced instructional design between competition and imagination is essential to preserve human agency amidst the rising dominance of Artificial Intelligence.